Optimization of PFC cuk converter parameters design for minimization of THD and voltage ripple - M. A. Z. A. Rashid; A. Ponniran; M. K. R. Noor; J. N. Jumadril; M. H. Yatim; A.N. Kasiran (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the optimization of PFC Cuk converter parameter design for the minimization of THD and voltage ripple. In this study, the PFC Cuk converter is designed to operate in discontinuous conduction mode (DCM) in order to achieve almost unity power factor. The passive components, i.e., inductor and capacitor are designed based on switching frequency and resonant frequency. Nevertheless, the ranges of duty cycle for buck and boost operations are 0<D<0.5 and 0.5<D<1, respectively for the output voltage variation of the converter. The principle of the parameters design optimization is based on the balancing energy compensation between the input capacitor and output inductor for minimization of THD current. In addition, the selection of high output capacitance will minimize the output voltage ripple significantly. A 65 W PFC Cuk converter prototype is developed and experimentally tested to confirm the parameters design optimization principle. The experimental results show that the THD current is reduced to 4.5% from 61.3% and the output voltage ripple is reduced to 7 V from 18 V after parameters optimization are realized. Furthermore, it is confirmed that the output voltage ripple frequency is always double of the input line frequency, 50 Hz and the output voltage ripple is always lower than the maximum input voltage ripple.